Virtual ER, a Serious Game for Interprofessional Education to Enhance Teamwork in Medical and Nursing Undergraduates: Development and Evaluation Study - Janet Yuen-Ha Wong; Joanna Ko; Sujin Nam; Tyrone Kwok; Sheila Lam; Jessica Cheuk; Maggie Chan; Veronica Lam; Gordon T C Wong; Zoe L H Ng; Abraham Ka-Chung Wai (JMIR Publications, 2022)
BackgroundEngaging students in interprofessional education for higher order thinking and collaborative problem-solving skills is challenging. This study reports the development of Virtual ER, a serious game played on a virtual platform, and how it can be an innovative way for delivering interprofessional education to medical and nursing undergraduates. ObjectiveWe report the development of a serious online game, Virtual ER, and evaluate its effect on teamwork enhancement and clinical competence. We also explore if Virtual ER can be an effective pedagogical tool to engage medical and nursing students with different learning styles. MethodsVirtual ER is a custom-made, learning outcome-driven, case-based web app. We developed a game performance scoring system with specific mechanisms to enhance serious gaming elements. Sixty-two students were recruited from our medical and nursing programs. They played the games in teams of 4 or 5, followed by an instructor-led debriefing for concept consolidation. Teamwork attitudes, as measured by the Human Factors Attitude Survey, were compared before and after the game. Learning style was measured with a modified Honey and Mumford learning style questionnaire. ResultsStudents were satisfied with Virtual ER (mean satisfaction score 5.44, SD 0.95, of a possible 7). Overall, Virtual ER enhanced teamwork attitude by 3.02 points (95% CI 1.15-4.88, P=.002). Students with higher scores as activists (estimate 9.09, 95% CI 5.17-13.02, P<.001) and pragmatists (estimate 5.69, 95% CI 1.18-10.20, P=.01) had a significantly higher degree of teamwork attitude enhancement, while students with higher scores as theorists and reflectors did not demonstrate significant changes. However, there was no difference in game performance scores between students with different learning styles. ConclusionsThere was considerable teamwork enhancement after playing Virtual ER for interprofessional education, in particular for students who had activist or pragmatist learning styles. Serious online games have potential in interprofessional education for the development of 21st century life skills. Our findings also suggest that Virtual ER for interprofessional education delivery could be expanded locally and globally.